Selênio como suplemento para bovinos intoxicados cronicamente por Pteridium sp. no Espirito Santo - Lanna Neta, Alda Trivellato (2018)
Pteridium sp. (bracken fern) is a plant responsible for several cases of intoxication in animals and humans. In bovines, one of the common conditions in the southern region of Espírito Santo is enzootic bovine hematuria (EBH) that doesn’t have treatment. Thus, the aim of the present study was to determine the effects of selenium associated with vitamin E supplementation in animals chronically poisoned by Pteridium sp. Twenty-one animals chronically intoxicated by the plant and with EBH were selected. The animals were clinically examined to confirmation of hematuria and collection of urine. The experimental design was done in four randomized groups (control – saline solution, treatment 1 - 0.05 mg.Kg-1 of the supplement, treatment 2 - 0.10 mg.Kg-1 of the supplement and treatment 3 - 0.20 mg.Kg-1 of the supplement. Parenteral supplementation was given intramuscularly once a week for 13 weeks. Biologically the animals were clinically evaluated and blood samples were collected for analysis of levels of serum selenium. Selenium analysis was done at the initial moments, before the supplementation (M0), after four weeks of treatment (M4), after eight weeks (M8) and after 12 weeks (M12), atomic absorption spectrophotometry method. The analysis of variance (ANOVA) followed by the Tukey test at 5% was used. It was verified that there was greater gain of weight of the animals treated with selenium and vitamin E in relation to the control group and, also, between the groups. The intensity of hematuria reduced from the sixth week and there was a significant difference between the treated groups and the control group, as well as between the groups. There was a significant difference in serum selenium concentration between treatments. Thus, it is concluded that selenium associated with vitamin E as a supplement for bovines chronically intoxicated for Pteridium sp. with EBH in Espirito Santo had a dose-dependent effect on the improvement of the clinical condition, causing a reduction in the intensity of hematuria and an increase in weight gain